Asupan karbohidrat, status gizi dan kebugaran jasmani siswa sekolah dasar di kota Kupang - Putu Amrytha Sanjiwani; Asweros Umbu Zogara (Poltekkes Kemenkes Kupang, 2020)
Background: Physical fitness is one important indicator of health, because it has function as predictor not only for cardiovascular problem and other diseases but also indicate of academic achievement and psychosocial problem. Nutrition is one of determinant factor of physical fitness through supply energy for physical activity. Carbohydrate is the biggest energy supply for body, specifically glucose for rapid energy supply and glycogen for energy saving. Glycogen will use when body lack of glucose in the blood to supply energy for activity. Objective: to analysis correlation between carbohydrate intake and nutritional status with physical fitness among school children Methods: This study was Cross-sectional study with 204 elementary school children became from 11 elementary school in Kupang city. Measurement of carbohydrate intake used 24-h recall and was analysed by Nutrisurvey application. Measurement of nutritional status used WHO BMI for age z-score and measurement of physical fitness used Harvard Step Test. Spearman rho test for analyse correlation between carbohydrate intake and nutritional status with physical fitness. Results: The prevalence of wasting was 23.5%, and 43.6% of respondents had severe deficit carbohydrate intake. Mostly of the children (>70%) had either good or excellent fitness index. Spearman rho test showed significant positive correlation between carbohydrate intake with physical fitness (r = 0.165, p=0.029) and no significant correlation between nutritional status with physical fitness (r = -0.103, p=0.143) Conclusion: There was significant positive correlation between carbohydrate intake with physical and no significant correlation between nutritional status with physical fitness.